2010
DOI: 10.1039/b912284b
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnS nanospheres: a high activity heterogeneous catalyst for synthesis of 5-substituted 1H-tetrazoles from nitriles and sodium azide

Abstract: Mesoporous ZnS nanospheres is a novel heterogeneous catalyst for synthesis of 5-substituted 1H-tetrazoles from various nitriles and sodium azide with excellent catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…ZnS is one of the very important materials applied in organic synthesis with excellent catalytic activity [3]. In 2010, Lang et al have been used mesoporous ZnS nanospheres as a new heterogeneous catalyst for the synthesis of 5-substituted 1H-tetrazole derivatives from various nitriles and sodium azide in DMF as a solvent [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnS is one of the very important materials applied in organic synthesis with excellent catalytic activity [3]. In 2010, Lang et al have been used mesoporous ZnS nanospheres as a new heterogeneous catalyst for the synthesis of 5-substituted 1H-tetrazole derivatives from various nitriles and sodium azide in DMF as a solvent [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrazoles and their derivatives have gained considerable attention because they have a wide range of applications in information recording systems in material science [1], medicinal chemistry [2], photography [3] and agriculture [4]. Pharmaceutical applications of tetrazoles include antiallergic, antimicrobial, sedatives [5], anti-inflammatory [6], anti-HIV [7], hormonal [8], lipophilic spacers [9] and diuretics activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was established, that yield of the desired product is determined by various factors: the temperature range (30-115°С), the ratio of the initial reagents (1:1 to 1:3), the catalyst basicity (mono-, di-, and trialkylamine hydrohalides, tetraalkylammonium halides), the nature of the solvent, the presence of acids, and reaction time. It was shown that tetrazole 35 was formed with nearly quantitative yield by the interaction of the starting compounds in the ratio 1:3 in the presence of di-or triethylamine hydrochloride in toluene, nitrobenzene, or xylene at temperature 95-100°С and reaction time 30 h. The similar reaction was discussed in the work of Lang et al 9 The usage of zinc sulfate nanospheres as a catalyst distinguished this reaction from the one above. In addition, a comparative assessment was carried out of the effect of other catalysts (zinc chloride, bromide, acetate, oxide, sulfide, and tungstate), solvent, and reaction time on the yield.…”
Section: Methodsmentioning
confidence: 71%
“…S2, S3 (see the Supporting Information). The isotherm characterize the type IV curve with a hysteresis loop usually generated by capillary condensation, which indicated that the ZnS nanospheres is typical of mesoporous materials [27,37]. The specific surface area and pore volume were determined to be about 135 m 2 g À1 and 0.44 cm 3 g À1 , respectively.…”
Section: Characterization Of Layer-by Layer Functionalized Porous Znsmentioning
confidence: 99%